STRATEGI BUSINESS TO BUSINESS (B2B) DALAM MANAJEMEN BISNIS PERUSAHAAN - JONATHAN, ALBERTUS (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Development of online technologies give birth to many types of businesses including business online. Various forms of this online business including Business to Business (B2B). B2B is a typical business that connects between business actors in a business transaction. The existence of the practice of B2B it has significance in the economy because it can improve the efficiency and effectiveness of business processes and can finally give birth to competitiveness. There are various characteristics of B2B based on various perspectives of the parties involved. Characteristics of B2B is also based on the characteristics of his website. Difference website used affects the parties involved in the B2B and it practices that distinguish the characteristics of any B2B. is the arranging some sellers with many buyers, Independent industry marketplaces that bring together many of the B2B sellers and many buyers.